Dihydrotanshinone I Specifically Inhibits NLRP3 Inflammasome Activation and Protects Against Septic Shock In Vivo - Wei, Ziying; Zhan, Xiaoyan; Ding, Kaixin; Xu, Guang; Shi, Wei; Ren, Lutong; Fang, Zhie; Liu, Tingting; Hou, Xiaorong; Zhao, Jia; Li, Hui; Li, Jiayi; et al. (Frontiers in Pharmacology, 2021)
The abnormal activation of NLRP3 inflammasome is closely related to the occurrence and development of many inflammatory diseases. Targeting NLRP3 inflammasome has been considered an efficient therapy to treat infections. We found that Dihydrotanshinone I (DHT) specifically blocked the canonical and noncanonical activation of NLRP3 inflammasome. Nevertheless, DHT had no relation with the activation ofAIM2 or NLRC4 inflammasome. Further study demonstrated that DHT had no influences on potassium efflux, calcium flux, or production of mitochondrial ROS. We also discovered that DHT suppressed ASC oligomerization induced by NLRP3 agonists, suggesting that DHT inhibited the assembly of NLRP3 inflammasome. Importantly, DHT possessed a significant therapeutic effect on NLRP3 inflammasome-mediated sepsis in mice. Therefore, our results clarify DHT as a specific small-molecule inhibitor for NLRP3 inflammasome and suggest that DHT can be conducted as a potential drug against NLRP3 mediated diseases.